Reasons for Failure of Antifungal-lock Therapy with Caspofungin: Need for Higher Concentrations - Rana İşgüder; Gökhan Ceylan; Özlem Sandal; Ferhat Sarı; Gamze Gülfidan; Bengü Demirağ; Hasan Ağın; İlker Devrim (Galenos Yayinevi, 2017)
Antifungal-lock therapy (AfLT) has arrived as an investigational approach for preventing catheter removal with limited clinical evidence of its efficiency. The principle of AfLT consists of catheter lumen replenishment by a selected antimicrobial agent and then locking it for an alternative treatment to eradicate the microbes embedded in endoluminal biofilms. Herein, we report a pediatric hematology-oncology patient with Candida parapsilosis-related central venous access device infection in which catheter removal was performed despite the systemic and intraluminal caspofungin treatment. For now, we recommend higher doses of caspofungin for AfLT especially in Candida parapsilosis-related catheter infections.